Studies in rats of a target specific and reversible general anesthetic with a favorable safety profile - Zheng Xie; Robert Fong; Aaron P. Fox (PLoS ONE, 2025)
Delirium and cognitive decline are linked to clinically relevant anesthetics in the vulnerable elderly population, prompting the need for new and safer anesthetic strategies. Most general anesthetics potentiate the activity of GABA A receptors. However, these drugs act on myriad other targets, causing unwanted effects. Dexmedetomidine (Dex), a selective α 2 adrenergic receptor agonist, is associated with reduced incidences of delirium and cognitive decline in the elderly. Unfortunately, despite its sedative effect, Dex is not suitable for general anesthesia when used alone. We previously demonstrated that enhancing Dex with low doses of either sevoflurane or propofol resulted in a potent general anesthetic that was rapidly reversible. In this study we assessed whether Dex enhanced by magnesium (Mg 2+ ) infusion could produce a general anesthetic. Mg 2+ is an essential ion in the body, possessing sedative effects attributable to antagonizing NMDA receptors and voltage-gated Ca 2+ channels and it may indirectly potentiate GABAergic signaling. Mg 2+ has been shown to be neuroprotective and safe to use even in pregnant women. Mg 2+ is a safer adjunct agent than either sevoflurane or propofol. For this study, rats of both sexes were anesthetized with a combination of Dex and Mg 2+ and then underwent procedures to determine the efficacy of the anesthetic. Dex with Mg 2+ produced an effective general anesthetic that was reversed by a combination of low dose atipamezole, an α 2 competitive antagonist, and caffeine. We compared Dex supplemented with Mg 2+ to Dex supplemented with midazolam, a selective positive GABA A modulator and found that immobility, antinociception, EEG signatures, and hemodynamic profiles were comparable. Our findings showed that activation of α 2 receptors by Dex, with blockade of NMDA receptors/ Ca 2+ channels by Mg 2+ produce an effective and reversible general anesthetic with possible neuroprotective properties that may be appropriate for cognitively vulnerable patients like the elderly.